Development and Validation of HPLC-MS/MS Method for Busereline Quantitation in Animal Blood Plasma - E. N. Fisher; E. S. Melnikov; I. Е. Shohin (Разработка и регистрация лекарственных средств)
Introduction. Busereline, being a synthetic gonadotropin-releasing hormone analog, is widely used for hormone-dependent cancer treatment (e.g. prostate cancer and breast cancer). Based on the accumulated scientific data for busereline quantitation in biosamples, the main analytical method that is used for this purpose is high-performance liquid chromatography (HPLC) with fluorescence detection, combined with protein precipitation (TCA 10%) for sample preparation. However, due to several limitations of this method resulting in low sensitivity (at the µg/mL level of concentrations), the HPLC-MS/MS analytical method was chosen for peptide determination in biosamples. The HPLC-MS/MS method is considered to have higher accuracy and specificity. The main sample preparation method for gonadotropin-releasing hormone analogs is solid-phase extraction. In our work, we’ve chosen protein precipitation as an alternative – easier and less laborious biosamples preparation process.Aim. The main objective of this study was the development and validation of HPLC-MS/MS method for busereline quantitation in animal (mini pigs) plasma samples and its further application to pharmacokinetic studies.Materials and methods. Busereline quantitative determination in plasma samples was performed using HPLC-MS/MS method. A protein precipitation procedure (methanol, 1:2, v/v) was used for busereline extraction from pig plasma.Results and discussion. The developed analytical method was validated for selectivity, linearity, matrix effect, accuracy (intra-day, inter-day), precision (intra-day, inter-day), LLOQ, carryover and stability.Conclusion. A new HPLC-MS/MS method for busereline quantitation in blood plasma was developed and successfully validated. The developed method showed linearity over the quantitation range from 1 to 20 ng/mL. The developed method can be successfully applied to busereline pharmacokinetic studies.